ANALISIS KESUKSESAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) BERDASARKAN MODEL DELONE DAN MCLEAN 2003 (STUDI PADA SATUAN KERJA PERANGKAT DAERAH KOTA LANGSA) - Wahyu Gustyari; Riha Dedi Priantana; Devi Satria Saputra (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this study was to analyze the SIMDA application using Delone and Mclean (2003) theory. The variables in the Delone and Mclean (2003) model are system quality, information quality, service quality, and intention to use in user satisfaction. The population in this study were all Regional Work Units (SKPD) in the Langsa City area of Aceh. The sampling technique of this study used non-probability sampling. Respondents who became the object of this study were the parties most responsible for the SIMDA so that 76 respondents. Data analysis using multiple linear regression with SPSS 21. The results of this study indicate that (1) system quality, information quality, service quality, and user interest simultaneously affect user satisfaction, (2) system quality partially affects user satisfaction, (3) information quality partially affects user satisfaction, (4) service quality partially affects user satisfaction, (5) user interest partially affects user satisfaction. The results indicate that the SIMDA application is quite successful.